Peran Guru dalam Membangun Motivasi Belajar Anak Usia Dini di TK PGRI Ibadurrahman Mande Kota Bima - Indrawati, Indrawati; Ilham, Ilham; Muslim, Muslim; Ahmad, Ahmad (UIR PRESS, 2024)
Low learning motivation will affect the level of children's achievement in the learning process, thus teachers are required to be able to solve the problem of low children's learning motivation. The purpose of this study was to examine the role of teachers in generating early childhood learning motivation at TK PGRI Ibadurrahman Mande, Bima City both in the learning process and outside of learning. The method used is qualitative with a field approach, data collection techniques in the form of observation, interviews and documentation and data analysis using techniques pioneered by Miles and Huberman. The results with the concept of constructive learning can provide stimulation to children so that they have high learning motivation. The concept of constructive learning includes learning outside the classroom (out class), utilisation of technology and exploration of nature. Then the teacher's applicable steps in maintaining children's learning motivation are by involving the role of the family to always create a learning space in every activity. In addition to the challenges faced by children such as, peers, family environment, technological advances and the school environment, in fact the concept of constructive learning by involving the role of the family is able to maintain children's learning motivation while having a high spirit of learning.